Accelerating Diffusion‐Ordered NMR Spectroscopy by Joint Sparse Sampling of Diffusion and Time Dimensions1. Issue 25 (24th April 2014) - Urbańczyk, Mateusz; Koźmiński, Wiktor; Kazimierczuk, Krzysztof
Abstract Diffusion‐ordered multidimensional NMR spectroscopy is a valuable technique for the analysis of complex chemical mixtures. However, this method is very time‐consuming because of the costly sampling of a multidimensional signal. Various sparse sampling techniques have been proposed to accelerate such measurements, but they have always been limited to frequency dimensions of NMR spectra. It is now revealed how sparse sampling can be extended to diffusion dimensions.